Food choice experiments with cadmium nitrate dosed food in terrestrial isopod Oniscus asellus (Crustacea) - Iskender Kaschl, Ulf (Acta biologica slovenica, 2002)
The influence of different concentrations of cadmium nitrate on food choice behaviour was studied in the terrestrial isopod Oniscus asellus: In paired food chaice tests, consumption rates were compared in relation to cadmium nitrate concentrations and duration of feeding. The consumption of contaminated, food was reduced at even the lowest cadmium concentration already in the first week of feeding. In the third week the consumption rates for uncontaminated and contaminated food reached a ratio of 6:4 in all animal groups. Consumption of contaminated food during the experiment resulted in increased cadmium content in the animals, It is presumed that O. asellus cannot distinguish food aocording to cadmium concentration. The difference in consumption rates between uncontaminated and cadmium-contaminated food could be based on integration of feeding behaviour and the adverse metabolic effectsof cadmium.
Keywords: Analysis; Cadmium; Cadmium Compounds; Crustacea; enakonožci; Feeding Behavior; Food Contamination; hrana; Hrana, onesnaženje; Hranjenje, vedenje; Kadmij; Kadmijeve spojine; onesnaževanje; Soil; Zemlja; zoologija